Visual Input in Simultaneous Interpreting - Rennert, Sylvi (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2008)
AbstractThis article looks at the interaction of the visual and the verbal in simultaneous interpreting, describing the significance of different elements of visual nonverbal communication with focus on those that facilitate understanding or need to be rendered in some way in the interpretation. While studies show that this visual information is often redundant, it can nevertheless aid the processing of verbal information. Visual contact can certainly be of importance when the verbal message refers to something visible to the audience or when the nonverbal adds information not present in the verbal message. A small experiment was conducted at the University of Vienna in order to determine whether there were any appreciable differences in interpreting with and without visual contact. The descriptive analysis sought to identify types of visual nonverbal communication that were particularly important for understanding the message.